PERANCANG BRAKE PEDAL ARM BERBAHAN HDPE (HIGH DENSITY POLYETHYLENE) DENGAN TEKNIK PEMBUATAN FDM (FUSED DEPOSITION MODELLING) UNTUK MOBIL SOEDIRMAN II - Arsyad Waasthia Ardani (2021)
The brake pedal on Sudirman I's car, the pedal used for the braking system still uses steel material, then the difficulty of manufacturing in making pedals using aluminum material is one of the factors of this problem. Using the FDM method on the Sudirman II car brake pedal to overcome manufacturing difficulties. In this final project, a design related to the brake pedal arm that will be used for Sudirman II car will be carried out using 3D printing with HDPE material. From the calculation results, the compressive force needed to stop the car at a speed of 50 km/hour with a braking distance of 15 meters on a car without a driver, with a minimum driver weight of 70 kg, and a maximum driver weight of 80 kg is 76.3622 N, 126,140 N, 133.260 N. And the results obtained in the simulation with a load used of 133,260 N and looking for optimization there are two designs, namely the initial design and the final design. The pedal design used in Sudirman II is the final design, apart from its light weight, this pedal can be used because it is able to withstand dynamic loads with a safety value of 4.3.